Populärvetenskapligt skrivande vidgar perspektivet och ökar förståelsen - Pelger, Susanne (Högre utbildning, 2011)
The capacity to explain subject matter to a non-specialist audience is one of the highest valued generic skills among science alumni of Lund University. Despite this fact, popular science communication is only poorly practiced during the undergraduate studies. In an earlier study we analysed the quality of popular science papers written by degree project students of biology. Our major observation was that most students had difficulties in changing perspectives, and in arguing the importance and relevance of their findings. In the project report we discussed the potential of popular science writing as a didactic tool. This is the main issue of the present article, which focuses on students’ own experiences of writing for the general public. Through a web-based questionnaire 64 biology students have described what contribution the popular writing on their degree project has had to their learning. A vast majority expressed that the writing helped them change perspectives and see their discipline and project in a different light. Many of the students described that the popular science writing made it easier for them to see the bigger picture, to better understand the aim of their own work, and to realize what implications their results might have in the future. The students were also asked whether the popular science writing contributed to their understanding of the discipline. Even though less students were able to describe such a relationship, their answers altogether support the idea that the genre contributes to their understanding as well. My concluding remark is therefore that popular science writing is a useful tool for reflection, and that it would add significant value to the students’ capacity of changing perspectives, and accordingly to a deeper understanding of the discipline in a broad sense.